Coordinated Planning of Interconnected Multi-Regional Power Systems Considering Large-Scale Energy Storage Systems, Transmission Expansion, and Carbon Emission Quota Trading - Jia Liu; Biao Jiang; Zao Tang; Pingliang Zeng; Tong Su; Yalou Li; Qiuwei Wu (CSEE Journal of Power and Energy Systems)
Global warming has motivated the world's major countries to actively develop technologies and make policies to promote carbon emission reduction. Focusing on interconnected multi-regional power systems, this paper proposes a coordinated planning model for interconnected power systems considering energy storage system planning and transmission expansion. A market-based carbon emission quota trading market that helps reduce carbon emissions is built and integrated into the coordi-nated planning model, where entities can purchase extra or sell surplus carbon emission quotas. Its effects on promoting carbon emission reduction are analyzed. Considering the limitations on information exchange between interconnected regional power systems, the proposed model is decoupled and solved with the analytical target cascading algorithm. A modified two-region 48-bus system is used to verify the effectiveness of the proposed model and solving method.